Spatial variability of soil acidity attributes and liming requirement for conilon coffee - Oliveira de Jesus Santos, Eduardo; Gontijo, Ivoney; Barreto da Silva, Marcelo (Coffee Science - ISSN 1984-3909, 2014)
The soils of Espírito Santo State are low natural fertility level, which frequently limit crop yields due to deficiencies of some soil elements, however, it presents high production potential. The purpose of this work was to describe the spatial variability of attributes related to soil acidity (pH, potential acidity, aluminum, calcium, magnesium), organic matter and liming requirement in a conilon coffee plantation (Coffea canephora Pierre) in a typical dystrophic Yellow Latosol (LAd). The study was carried out in a farm area, in the Northern part of the state of Espírito Santo, Brazil. The experimental area was 20 x 61.6 m (1.232 m2) in a regular grid where 60 samples were equally spaced in grids of 5.6 x 5 m, at a soil depth of 0-20 cm. All property semivariograms disclosure were satisfactorily described by spherical model with a moderate and strong spatial structure with ranges of spatial structure varying from 8.0 m to 33.58 m.